Manajemen Pembelajaran Ekstrakurikuler dalam Meningkatkan Mutu Madrasah - Nur Arifah (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2016)
Based on constitution number 20 year 2003 about National Education System and Permendikmas number 39 year 2008 about coaching students, chapter one, clause one, paragraph (a), which reads develop potential students in an optimal and integrated matching with the talent, enthusiasm, and creativity. Paragraph (c) reads actualize the potential of students in achieving seeded according to their talents and interests. Based on this, the school needs to establish a special container to improve the talent, potential and creativity of students so as to support school improvement.